Ocena finansowania inwestycji rolniczych leasingiem - Szafraniec-Siluta, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
This article aims to assess the financing of agricultural farms in Poland with leasing in the context of the global financial crisis, encouraging individual companies to use internal sources of funding to a greater extent than from external sources. Analysis and assessment of changes in the value of all leased assets and the value of leased machinery cover the period 2005–2009. The period of the worsening of the economic crisis (2008 – first quarter 2010) was supplemented with an indication of the dynamics of changes in the value of items in lease of statistical data of the Polish Association of Leasing. During the economic slowdown, companies have limited investment financing by leasing. However, the value of agricultural machinery leased was increasing throughout the period considered, which means that leasing is an attractive form of financing investment for farms.